Demographic profiling of life insurance ownership in the northern regions of Malaysia - Lim, Chee Chee; Tan, Suang Sin (Universiti Malaysia Sarawak, 2019)
The paper aims to provide the demographic profiling of life insurance ownership in the northern regions of Malaysia that could be generalized to the whole of Malaysia so that efforts could be taken to raise the market penetration rate of life insurance by insurers in promoting the purchase of life insurance to individuals who have not owned life insurance yet. A structured questionnaire was used to collect data through stratified random sampling to enable generalization of findings. The data were subject to binary logistic regression analysis. The major findings show that gender, education, ethnicity and income have a significant relationship with life insurance ownership. Life insurance policyholders (in the northern regions) of Malaysia are more likely the males, highly educated individuals, the Chinese and middle income earners. The paper proposes that efforts be taken to identify and encourage the females, less educated individuals, non-Chinese and low income earners who have not owned any life insurance to purchase one. The paper suggests that future studies can consider other geographical areas of Malaysia or the whole of Malaysia in demographic profiling for conventional and Islamic life insurance ownership separately, and for their different types of life insurance products.